THE RELATIONSHIP BETWEEN LEARNING INTEREST, LEARNING INDEPENDENT AND LEARNING FACILITIES AT HOME TOWARD MATHEMATICS LEARNING OUTCOMES - Helda Riska Setiarini; Sumargiyani Sumargiyani (Universitas Ahmad Dahlan, 2018)
The results of students' mathematics learning associated with many factors. Learning interest, learning independent, and learning facilities at home is factors that may be related to mathematics learning outcomes of students. This study aims to determine whether or not a positive and significant relationship between learning interest, learning independent learning facilities at home with mathematics learning outcomes in students class VIII at SMP Muhammadiyah Pakem Sleman on the even semester of the academic year 2016/2017.The population in this study was all eighth-grade students at SMP Muhammadiyah Pakem Sleman on even semester of the academic year 2016/2017 which consists of 4 classes with a total of 152 students as a sample class was class VIII A, which includes of 37 students using a random sampling technique to the class. Methods of data collection used questionnaires and testsâ€”the instruments using validity, reliability testing, and different test power. Test requirements analysis was used the normality test, the independent test, and the linearity test. Data analysis for hypothesis testing used correlation analysis and linear regression analysis. The results showed that there is a positive and significant relationship between the learning interest (X1), learning independent (X2), and learning facilities at home (X3) with mathematics learning outcomes with Â means Â with R = 0,7114 and R2 = 0,5061 with , and RC(X1) = 34,4358 %, RC(X2)= 36,4429 %, and RC(X3)= 29,1214 %, EC(X1) = 17,4279 %, EC(X2) = 18,4437 %, and EC(X3)= 14,7383 %.